Human Resource Practices in Public Healthcare Sector: A Perceptual Study among Healthcare Professionals - Sumathi G N (Intelektual Pustaka Media Utama, 2017)
The study is aimed to identify various human resource practices in the public healthcare sector and to measure the level of human resource practices. The study adopts the perceptual view of healthcare professionals such as medical officers and staff nurses working in Primary Health Centres of Tamilnadu. A survey using a questionnaire is used to collect data from healthcare professionals. The results indicated that human resource practices such as job autonomy and job security are perceived to be useful and necessary, while training and performance management system are found to provide necessary inputs for carrying job duties and practices such as career growth opportunities and compensation need the attention of the officials of Health and Family Welfare department of Tamilnadu Government for enhancing the utility of these practices.